ANALISIS PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PADA PT. KAHATEX CABANG RANCAEKEK - Pertiwi, Fitria Budi; Imroni, Asep (JURSIMA, 2024)
The reason this research was carried out was to improve the performance of PT. kahatex Rancaekek branch with factors of influence of work environment, work motivation and work discipline. One of the factors that affect performance is work motivation at PT. Kahatex. This work motivation can improve the performance ability of PT. Kahatex Rancaekek researchers found that there is bonus income for employees if they reach the target set by the company. Chairman at PT. Kahatex holds holiday tours every year. So this is related between work motivation to employee performance. This research is with a quantitative descriptive approach. Data collection techniques were used by distributing questionnaires using a sample of 30 employee respondents, and conducting interviews with leaders or employees at PT. Kahatex Rancaekek Branch. The technique in collecting data is to use the SPSS application version 22 where the data will be analyzed by testing multiple liner regression. The results of this study show that the t-test variables of work environment (X1), work motivation variables (X2), and work discipline (X3) have a positive and significant effect on employee performance. And test F variables work environment (X1), work motivation variables (X2), and work discipline (X3) have a positive and significant effect on employee performance.